Bioimpedance Body Measures and Serum Lipid Levels in Masculine Depression - von Zimmermann, Claudia; Brückner, Lena; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is a main reason for suicide, and serum lipids are involved in both affective disorders and related suicidal behavior. Moreover, masculine depression has been suggested as a subtype of depression with an increased risk for suicide. Here, we studied the relationship between body measures, serum lipids, suicidal thoughts, and masculine depression. Methods: Depressed patients (44% women) were divided by a sex-separated median-split into a group of 81 “patients with masculine depression” (mean age ± standard error: 36.4 ± 1.6 years) and a group of 82 “patients with non-masculine depression” (age 45.7 ± 1.6 years) according to the Male Depression Risk Scale. We compared body measures, serum lipid levels, and past suicidal ideation between these groups and explored differences between these groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years). Results: Patients with masculine depression did not significantly differ from patients with non-masculine depression in any of the body measures, lipid markers, or suicidal thoughts. Compared to healthy controls, both patient groups showed significantly higher body fat (B[masculine depression] = 0.041 and B[non–masculine depression] = 0.050), lower high-density lipoprotein (HDL) cholesterol (B = –0.045 and –0.044), and a higher risk for suicidal thoughts (B = 3.927 and 2.663) than healthy controls. Suicidal thoughts were significantly associated with lower low-density lipoprotein (LDL)/HDL ratios (B = –0.455) in patients with depression and with higher LDL cholesterol levels (B = 0.020) in healthy controls subjects. Limitation: Correlational study design and focus on in-patients. Conclusion: In the studied cohort, masculine depression was not significantly associated with the analyzed parameters of body measures, serum lipids, or suicidal thoughts in in-patients with depression.
CRIS-Team Scopus Importer:2022-08-12
Keywords: body fat; cholesterol; masculine depression; serum lipids; suicidal behavior

Body mass index and serum levels of soluble leptin receptor are sex-specifically related to alcohol binge drinking behavior - Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes; Weinland, Christian; Lenz, Bernd (Psychoneuroendocrinology, 2021)
Objective: Binge drinking is a highly prevalent behavior in adolescents and young adults and a risk factor to develop alcohol use disorder. Body mass index (BMI) and blood levels of leptin peptide and its soluble receptor have been implicated in alcohol use disorder; however, their role in binge drinking remains to be investigated. Method: We studied associations of BMI, serum levels of soluble leptin receptor (ObRe) and leptin as well as the free leptin index with binge drinking in 93 male and 99 female young adults. Results: In men, binge drinkers showed significantly higher BMI (kg/m2) than non-binge drinkers (23.67 vs. 22.08) and higher BMI correlated significantly with more severe binge drinking episodes (ρ = 0.251). In women, we found significantly higher ObRe (ng/ml) / BMI (kg/m2) values in binge drinkers than in non-binge drinkers (0.52 vs. 0.44) and ObRe/BMI values correlated significantly with more severe binge drinking episodes (ρ = 0.210). Conclusion: This study confirms that higher BMI associates with binge drinking in men and shows for the first time a role of ObRe/BMI in binge drinking in women. Our data emphasize the importance of further research in the ﬁeld of metabolic markers and implications in neurobiological processes of binge drinking.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alcohol binge drinking; Body mass index; Leptin; Soluble leptin receptor

Elevated Oxytocin Receptor Blood Concentrations Predict Higher Risk for, More, and Earlier 24-Month Hospital Readmissions after In-Patient Detoxification in Males with Alcohol Use Disorder - Mühle, Christiane; Mazza, Massimiliano; Weinland, Christian; von Zimmermann, Claudia; Bach, Patrick; Kiefer, Falk; Grinevich, Valery; Zoicas, Iulia; Kornhuber, Johannes; Lenz, Bernd (International Journal of Molecular Sciences, 2022)
Alcohol use disorder (AUD) is a major global mental health challenge. Knowledge concerning mechanisms underlying AUD and predictive biomarkers of AUD progression and relapse are insufficient. Recently, addiction research is focusing attention on the oxytocin system. However, to our knowledge, blood concentrations of the oxytocin receptor (OXTR) have not yet been studied in AUD. Here, in sex-separated analyses, OXTR serum concentrations were compared between early-abstinent in-patients with AUD (113 men, 87 women) and age-matched healthy controls (133 men, 107 women). The OXTR concentrations were correlated with sex hormone and oxytocin concentrations and alcohol-related hospital readmissions during a 24-month follow-up. In male patients with AUD, higher OXTR concentrations were found in those with an alcohol-related readmission than in those without (143%; p = 0.004), and they correlated with more prospective readmissions (rho = 0.249; p = 0.008) and fewer days to the first readmission (rho = -0.268; p = 0.004). In men and women, OXTR concentrations did not significantly differ between patients with AUD and controls. We found lower OXTR concentrations in smokers versus non-smokers in female patients (61%; p = 0.001) and controls (51%; p = 0.003). In controls, OXTR concentrations correlated with dihydrotestosterone (men, rho = 0.189; p = 0.030) and testosterone concentrations (women, rho = 0.281; p = 0.003). This clinical study provides novel insight into the role of serum OXTR levels in AUD. Future studies are encouraged to add to the available knowledge and investigate clinical implications of OXTR blood concentrations.
CRIS-Team WoS Importer:2022-09-23

Male depression syndrome is characterized by pronounced Cluster B personality traits - Sedlinská, Terezie; Mühle, Christiane; Richter-Schmidinger, Tanja; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of Affective Disorders, 2021)
Background: Male depression syndrome (Male-DS) refers to alternative depression symptoms related to the male sex, such as externalizing behaviors, emotional suppression, substance misuse, and risk-seeking. Although these symptoms contribute to gender bias in the diagnosis of depression, Male-DS can be found in both sexes. In this cross-sectional study, we analyzed associations between Male-DS and clinical personality accentuations. Methods: We compared clinical personality accentuations between 78 depressed patients with high Male-DS scores (46% women; mean age ± standard error of the mean: 36.5 ± 1.6 years) and 76 depressed patients with low Male-DS scores (43% women; age 44.8 ± 1.7 years). We also explored differences between the two patient groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years). Results: Depressed patients with high Male-DS scores showed stronger borderline (partial η2 0.121), impulsive (0.112), and antisocial (0.078) personality accentuations than those with low Male-DS scores after Bonferroni adjustment and controlling for sex, depression severity, and age. Relative to healthy controls, patients with high Male-DS values scored higher in all personality dimensions except for the narcissistic dimension. Patients with low Male-DS values scored higher in all Cluster A and C dimensions and the impulsive and borderline dimensions, but their scores were lower in the narcissistic dimension. Limitations: Cross-sectional design and focus on in-patients. Conclusions: We found pronounced Cluster B personality in patients with high Male-DS scores versus patients with low scores. Further prospective research is needed to verify that Cluster B personality traits represent a pre-morbid risk factor for Male-DS.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Antisocial; Borderline; Impulsive; Male depression; Personality

Masculine depression and its problem behaviors: use alcohol and drugs, work hard, and avoid psychiatry! - von Zimmermann, Claudia; Hübner, Magdalena; Mühle, Christiane; Müller, Christian P.; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (European archives of psychiatry and clinical neuroscience, 2023)
The gender role influences vulnerability to mental illness. Substance use, even critical in scale, is perceived as masculine, just like hard (over-)work, while not seeking help. With the ongoing separation between gender and sex, masculine norms become more relevant also to females’ mental health. The male depression concept highlights the role of male symptoms in affective disorders. However, the empirical evidence is still limited. Here, we use the denomination ‘masculine depression’ to open the category for female patients and tested substance use patterns, health services’ utilization, and working hours as predictors in a case–control study of 163 depressed in-patients (44% women; masculine vs. non-masculine depression according to a median split of the Male Depression Rating Scale-22) and 176 controls (51% women). We assessed higher depression severity in patients with masculine (vs. non-masculine) depression. Masculine depression (vs. non-masculine depression and vs. no depression) was predicted by more frequent and critical use of alcohol (including binge drinking), tobacco, and illicit drugs, and by longer working times. Moreover, fewer health services contacts due to mental complaints during the previous year were associated with masculine (vs. non-masculine) depression. Alarmingly, even critical substance misuse was not significantly associated with more frequent health services contacts; however, the higher the depression severity, the more contacts the patients reported. Here, we provide evidence that patients with masculine depression are highly burdened and undertreated, which applies equally to female and male patients. This study identified promising targets to establish specialized care offers.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcoholism; Drug use; Help seeking; Male depression; Masculine depression; Nicotine; Substance use

Meta-analytic evidence for a sex-diverging association between alcohol use and body mass index. - Siegmann, Eva-Maria; Mazza, Massimiliano; Weinland, Christian; Kiefer, Falk; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Scientific Reports, 2022)
Alcohol use is an important health issue and has been suggested to contribute to the burden produced by obesity. Both alcohol use and obesity are subject to sex differences. The available studies on the relationship between alcohol use and body mass index (BMI) report inconsistent results with positive, negative, and null findings which requests a meta-analytic approach. Therefore, we conducted a meta-analysis of case-control, cohort, and cross-sectional studies. The systematic literature search and data extraction was performed by 3 independent raters. We conducted sex-separated meta-analyses and -regressions to investigate how alcohol consumption associates with BMI. Our systematic literature search resulted in 36 studies with 48 data sets (Nmen = 172,254; kmen = 30; Nwomen = 24,164; kwomen = 18; Nunknown sex = 672,344; kunknown sex = 24). Alcohol use was associated with higher BMI in men (g = 0.08 [0.07; 0.09]) and lower BMI in women (g = - 0.26 [- 0.29; - 0.22]). Moreover, we found the amount of daily alcohol intake in men (β = 0.001 [0.0008; 0.0014]) and ethnicity in women (g[Caucasians] = - 0.45 versus g[Asians] = - 0.05; z = 11.5, p < 0.0001) to moderate these effects. We here identified sex-diverging relationships between alcohol use and BMI, found daily alcohol intake and ethnicity to sex-specifically moderate these effects, and argue that sex-specific choice of beverage type and higher amount of daily alcohol use in men than in women account for these observations. Future research is needed to provide empirical evidence for the underlying mechanisms.
EVALuna2:523162

Oxytocin blood concentrations in alcohol use disorder: A cross-sectional, longitudinal, and sex-separated study - Lenz, Bernd; Weinland, Christian; Bach, Patrick; Kiefer, Falk; Grinevich, Valery; Zoicas, Iulia; Kornhuber, Johannes; Mühle, Christiane (European Neuropsychopharmacology, 2021)
Alcohol use disorder (AUD) is a severe illness, for which we lack sufficient mechanistic understanding. Preliminary evidence associates AUD with the oxytocin (OXT) system. Here we investigated alterations in endogenous OXT blood concentrations in patients with AUD and their association with alcohol drinking and prospective course. In sex-separated analyses, OXT serum concentrations of 200 in-patients with AUD (56.5% male; baseline, 24–72 h of abstinence) were compared with those of 240 age-matched healthy controls (55.4% male), investigated longitudinally (follow-up, 5 days later), and tested for associations with alcohol drinking behavior and prospective 24-month alcohol-related hospital readmissions. At baseline, the patients showed increased OXT concentrations relative to controls (men, 156%, P < 0.001; women, 124%, P = 0.002). The elevations normalized at follow-up. In male patients, baseline OXT concentrations correlated positively with alcohol concentration at admission, the amount of alcohol consumption per drinking year, and the number of previous withdrawal treatments (Rho > 0.195, P < 0.044). In beverage type-specific analysis, baseline OXT concentrations correlated with liquor consumption positively in male and negatively in female patients (|Rho| > 0.277, P < 0.017). Higher baseline OXT concentrations predicted more readmissions and fewer days to the first readmission (|Rho| > 0.185, P < 0.050) in male patients. This study provides novel and sex-separated insights into the role of the OXT system in AUD. We identified a mechanism that might underlie the sex-separated choice of beverage type and established that increased OXT concentrations during early abstinence predict a worse outcome in male patients with AUD.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Alcohol dependence; Alcohol use disorder; Alcoholic beverages; Alcoholism; Ethanol; Oxytocin; Patient readmission; Prospective studies

Progesterone serum levels correlate negatively with craving in female postmenopausal in-patients with alcohol use disorder: A sex- and menopausal status-separated study - Weinland, Christian; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2021)
Objective: Alcohol use disorder (AUD) shows a high prevalence and often takes a severe and chronic course. However, the underlying mechanisms still need to be better understood. There is increasing evidence for a role of sex hormones in AUD and for the importance of sex-separated concepts in addiction research. Nevertheless, only few data give insight into how progesterone is involved in AUD. Method: Serum progesterone levels were measured at baseline (during early abstinence) in 186 in-patients with AUD (19% premenopausal females, 20% postmenopausal females, 61% males) and at median 5 days later. They were compared with those of 233 healthy control subjects (24% premenopausal females, 19% postmenopausal females, 57% males). We quantified craving with the Obsessive Compulsive Drinking Scale (OCDS) and visual analogue scales (VAS). Alcohol-related hospital readmissions within a 24-month period following initial in-patient treatment were recorded. We conducted analyses separately for sex and for menopausal status in female participants. Results: Postmenopausal females with AUD reported higher craving than premenopausal females. In postmenopausal females, higher baseline progesterone levels correlated with lower OCDS total craving and VAS craving, i.e., lower state craving and lower average, maximum, and less frequent craving during withdrawal. In males with AUD, progesterone levels at baseline tended to be higher than in controls and declined to follow-up. Alcohol-related readmissions were not significantly associated with serum progesterone levels. Conclusion: We provide first evidence that progesterone levels correlate with craving in females with AUD.
CRIS-Team Scopus Importer:2021-04-23
Keywords: AUD; Craving; Progesterone; Sex hormones

Psychometric properties of the German Penn Alcohol Craving Scale - Nakovics, Helmut; Hoffmann, Sabine; Koopmann, Anne; Bach, Patrick; Abel, Martin; Sommer, Wolfgang H.; Kiefer, Falk; Weinland, Christian; von Zimmermann, Claudia; Siegmann, Eva-Maria; Kornhuber, Johannes; Mühle, Christiane; et al. (Alcohol and Alcoholism, 2023)
Craving for alcohol is an important diagnostic criterion in alcohol use disorder (AUD) and an established predictor of future relapse. The 5-item Penn Alcohol Craving Scale (PACS) is one of the most widely used questionnaires to quantify craving and has been translated into different languages. It is assumed that the PACS constitutes one factor, although theoretical considerations suggest an additional second factor. We conducted stability and factor analyses (principal component and confirmatory factor analyses) of the German PACS (PACS-G) in samples of patients with AUD from the following three German study sites: Erlangen, N = 188 (mean age: 47.1 years, 43.5% female); Mannheim, N = 440 (45.5 years, 28.6% female); Hannover, N = 107 (48.1 years, 48.6% female). In our samples, the 2-factor solution of the PACS-G version is more stable than the internationally assumed 1-factor solution. The resulting two PACS-G subscores ‘difficulty to resist’ (items 4 and 5) and ‘thoughts about alcohol’ (items 1, 2, and 3) have an internal consistency (Cronbach’s alpha) of 0.80 ≤ α ≤ 0.90, m = 0.86 and 0.86 ≤ α ≤ 0.91, m = 0.89 with an overlap of R2 = 62%. We found good convergent validity assessed via the Craving Automatized Scale-Alcohol and the Obsessive-Compulsive Drinking Scale, but also correlations with depression and anxiety assessed via the Beck’s Depression and Anxiety Inventories. This study is the first to provide evidence for a 2-factor solution (‘difficulty to resist’ and ‘thoughts about alcohol’) underlying the PACS-G version.
CRIS-Team Scopus Importer:2023-12-15
Keywords: alcohol dependence; alcohol use disorder; craving

Sulphated dehydroepiandrosterone serum levels are reduced in women with alcohol use disorder and correlate negatively with craving: A sex-separated cross-sectional and longitudinal study - Weinland, Christian; Mühle, Christiane; von Zimmermann, Claudia; Kornhuber, Johannes; Lenz, Bernd (Addiction Biology, 2022)
Previous studies have established a role of sex hormones in alcohol use disorder (AUD).Only few clinical investigations with low numbers of patients with AUD have focused on the sulphated form of dehydroepiandrosterone (DHEA-S), despite its function as a neuromodulating sex steroid on receptors in the central nervous system (γ-aminobutyric acid type A, N-methyl-D-aspartate, sigma-1 receptors). DHEA-S serum levels were compared between 200 inpatients with AUD (44% women) admitted for withdrawal treatment and 240 healthy controls (45% women) and analysed longitudinally in patients from early abstinence (baseline) to a median of 5 days later. We also correlated DHEA-S levels with craving, liver enzyme activities, and prospective alcohol-related readmissions during a 24-month follow-up. DHEA-S concentrations were lower in female patients than in female healthy controls during baseline (70%) and decreased from baseline to follow-up in the female and male patients groups (down to: women, 92%; men, 76%). Baseline DHEA-S concentrations correlated with the total and obsessive subscales of the Obsessive–Compulsive Drinking Scale and with maximum visual analogue scale craving scores in female patients (Rho ≤ −0.240) and gamma-glutamyl transferase activity in female (Rho = −0.292) and male (Rho = −0.391) patients. DHEA-S did not significantly predict outcome. We found interactions with smoking behaviour and age. This is the first study based on large cohorts of inpatients with AUD undergoing a qualified detoxification treatment to provide sex-separated evidence for associations of DHEA-S serum concentrations with AUD and related phenotypes. The results stimulate further investigations whether DHEA-S directly influences alcohol craving building a basis to develop sex-sensitive prevention and treatment strategies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: AUD; craving; DHEA -S; relapse; sex hormones